(untitled) (Research, Society and Development, 2022)
Hospitalization interferes in the individual’s health in the long term, generating limitations and need for support, especially in the elderly. Social relationships and social support available to individuals in their daily lives are indicators of social integration and ensure support in times of crisis or readaptation, with positive effects on their health. The objective of this study was to evaluate the social support of hospitalized individuals, its relationship with other sociodemographic variables and with hospital outcomes. This is a quantitative, descriptive, longitudinal study. Social support was assessed through the question: “Can the patient count on someone to help or assist him or her?”. Adult and elderly individuals assessed by the Hospital Inpatient Complex Patient Identification Instrument were included. The sample included 1421 individuals, being identified that 93.6% had social support according to the analyzed variable. It was observed that elderly individuals and those at higher risk had proportional social support; however, there was no significant association with mortality or length of stay. The instrument succinctly assesses social support, and it is necessary to consider other sociodemographic variables for a more in-depth evaluation. Further studies are needed in order to identify social support, so that strategies can be directed to interventions capable of expanding health care.